2018
DOI: 10.3390/agronomy8060096
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Winter Wheat (Triticum aestivum L.) Seasonal Irrigation Amount, Evapotranspiration, Yield, and Water Productivity under Semiarid Climate

Abstract: A long-term field experiment was conducted from 2002 to 2014 for the evaluation of yield and water productivity of three winter wheat varieties-Kharkof, Scout 66, and TAM107-under sprinkler irrigation at New Mexico State University Agricultural Science Center at Farmington, NM. Winter wheat daily evapotranspiration was estimated following the United Nations Food and Agriculture Organization FAO crop coefficient approach (ETc = Kc ETo), and crop water use efficiency (CWUE), evapotranspiration water use efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
0
12
0
2
Order By: Relevance
“…According to Doorenbos [28], when the precipitation does not meet crop water requirement, IWUE is lower in the year of less precipitation. Payero et al [29] on maize's IWUE, Djaman et al [30] on wheat's IWUE, and Djaman et al [31] on maize's IWUE all demonstrated that IWUE decreased linearly with irrigation amount, both in wet or dry growing seasons, and IWUE in a wet year was higher than a dry year. Different from corn and wheat, our results showed that IWUE increased with irrigation amount, but the similar results show that IWUE in the wet year was higher than the dry year, where flue-tobacco IWUE varied from 0.…”
Section: The Relationship Between Iwue and Irrigation Amountmentioning
confidence: 96%
“…According to Doorenbos [28], when the precipitation does not meet crop water requirement, IWUE is lower in the year of less precipitation. Payero et al [29] on maize's IWUE, Djaman et al [30] on wheat's IWUE, and Djaman et al [31] on maize's IWUE all demonstrated that IWUE decreased linearly with irrigation amount, both in wet or dry growing seasons, and IWUE in a wet year was higher than a dry year. Different from corn and wheat, our results showed that IWUE increased with irrigation amount, but the similar results show that IWUE in the wet year was higher than the dry year, where flue-tobacco IWUE varied from 0.…”
Section: The Relationship Between Iwue and Irrigation Amountmentioning
confidence: 96%
“…The reason for this may be due to the increment of water content and heat capacity of the root layer soil caused by freezing irrigation. This prevented drastic changes in temperature in the alfalfa root zone before winter and provided good environmental conditions to acclimatize alfalfa to cold conditions, thus improving the alfalfa overwintering rate [70][71][72][73][74]. Also, repeated thawing and freezing of soil and the days and nights after freezing irrigation played a role in loosening the soil and improving alfalfa habitat conditions.…”
Section: Estimating the Source Contribution To Xylem Water After Freementioning
confidence: 99%
“…Bu nedenle uzun yıllık ölçümlerin değerlendirilmesi ve doğrudan ET ölçüm yöntemi olan tartılı lizimetre ile karşılaştırılması gerekir. Djaman et al, (2018), Adana gibi yarı kurak bir bölgede (New Mexico) 2002-2014 yılları arasında buğday bitkisi ile yaptıkları bir çalışmada konulara 511 mm ile 787 mm arasında sulama suyu uygulamışlardır. Su bütçesi yöntemine göre belirlenen bitki su tüketimleri konulara göre 625 mm ile 890 mm arasında değişmiştir.…”
Section: Etwb = I+ P + D ± R ± δSunclassified
“…2004, kışlık buğdayda, farklı sulama uygulamaları oluşturdukları çalışmalarında su kullanma randımanlarının 1.11-1.61 g.m -2 .mm -1 arasında değiştiğini bulmuşlardır. Djaman et al, (2018) tarafından yarı kurak bir iklimde farklı sulama konularının oluşturulduğu çalışmada, su kullanım randımanları 0.26-1.17 g.m -2 .mm -1 arasında değişmiştir. Sezen (2000) ise, Çukurova koşullarında buğday bitkisiyle yaptığı çalışmada su kullanma randımanlarının 0.66-1.50 g.m -2 .mm -1 arasında değiştiğini bulmuştur.…”
Section: Hi=unclassified